DEVELOPMENT AND EVALUATION OF CHRONOMODULATED DELIVERY SYSTEM OF METOCLOPRAMIDE HYDROCHLORIDE - Shenoy, Sandhya Rajendra; Jain, Pritam; Kulkarni, Madhur (International Journal of Applied Pharmaceutics, 2016)
Objective: Metoclopramide hydrochloride (meto) is indicated in the treatment of diabetic gastro paresis. It is also used in the treatment of pregnancy-induced morning sickness. Present work involved the development of a chrono-modulated delivery system of meto, intended to be taken at bedtime which would elicit the therapeutic response early in the morning when needed the most to prevent the symptoms of diabetic gastro paresis and morning sickness. Methods: Immediate release tablets of meto were prepared and optimized for disintegration time and in vitro drug release. Subsequently, these tablets were compression coated using various ratios of glyceryl dibehenate and diluents. The resulting tablets were evaluated for disintegration time and in vitro drug release. Optimized formulation was subjected to accelerated stability studies for 3 mo. Results: The optimized immediate release tablets exhibited disintegration time of 2-3 min and more than 90% drug release within 30 min. These tablets when compression coated with the optimized ratio of glyceryl dibehenate and di-calcium phosphate could delay the disintegration time to 251 min. In vitro release study of the tablets showed the lag phase of 4 h after which there was a complete drug release within 1 h. Accelerated stability studies indicated good physical and chemical stability of the formulation. Conclusion: Chrono-modulated formulation of meto could delay the release of the drug by four h. This lag in the release is expected to modulate the time of therapeutic response of meto early in the morning at 6-7 h interval after the administration of dosage form at bedtime.